Seeking Pieter Bruegel the Elder’s Father: Pieter Bruegel the Eldest (†1566), Pensioner in Sint-Janshuis Retirement Home, Bergen op Zoom - Zuijderduijn, Jaco (Early Modern Low Countries, 2020)
In 1553-1554, one Pieter Bruegel retired to Sint-Janshuis, Bergen op Zoom: a home where former servants of the Marquises of Bergen could spend their old age. The main argument of the article is that this retiree, who was the former barber-surgeon of Marquis Jan IV (1541-1567), should be considered as the father of the painter Pieter Bruegel the Elder. The latter’s origins are almost completely unknown, yet heavily debated: was he the son of a peasant who painted scenes of life in the countryside, or was he born and raised in an urban environment and did he satirise peasants in his artistic work? An historical reconstruction of the background of the retired barber-surgeon, and the retirement home he spent his final years in, shows he is a strong candidate for having fathered the famous painter. Evidence from the discipline of art history provides further support for the claim that the painter Pieter Bruegel the Elder was the son of a barber-surgeon and came from an urban social-middling-group background with close ties to one of the most important courts and artistic milieus in the Low Countries, the Renaissance palace Markiezenhof in Bergen op Zoom.